Cellulose Fibers Dissolution in Alkaline Solution - Mahdi, Yasmeen Salih; Mohammed, Asem Hassan; Mohammed, Alaa Kareem (Al-Khwarizmi Engineering Journal, 2019)
In this study, NaOH dissolution method was applied to dissolve cellulose fibers which extracted from date palm fronds (type Al-Zahdi) taken from Iraqi gardens. In this process, (NaOH)-solution is brought into contact with the cellulose fibers at low temperature. Experiments were conducted with different concentrations of NaOH (4%, 6%, 8% and12%) weight percent at two cooling bath temperatures (-15 oC) and (-20oC). Maximum cellulose dissolution was 23 wt% which obtained at 8 wt% concentration of NaOH and at cooling bath temperature of -20oC. In order to enhance the cellulose fibers dissolution, the sample was pretreated with Fenton's reagent which consists of hydrogen peroxide (H2O2), oxalic acid (C2H2O4) and ferrous sulfate (FeSO4). This reagent reacts with cellulose fibers and produces free radicals which increase cellulose dissolution. In this work three variables were studied: cooling bath temperature (-15oCand-20oC), NaOH concentration (4%, 6%, 8% and12%) and time of Fenton's reagent treatment (1-48) hrs. The results showed that the best percent of cellulose dissolution was (42 wt %) which occurred at treatment time (24 hours), temperature (-20oC) and NaOH concentration 8%. In another set of experiments urea was added to NaOH solution as a catalyst with proportion (6%NaOH+4% urea) at two temperatures -15 and -20 oC. The results show that the solubility of cellulose increase to 62% for the sample which treated with Fenton's reagent and to 35% for the untreated sample, both values were obtained at -15oC.